PENINGKATAN KOMPETENSI SISWA MENGGUNAKAN MEDIA MODEL BERBANTUAN LKS PADA PEMBELAJARAN BIOLOGI KELAS XI IPA3 SMA NEGERI I PASIR PENYU INDRAGIRI HULU PROVINSI RIAU - Indrawati - (Menara Ilmu, 2018)
This class action research was done to know the improvement of students competencyusing the media of students worksheet-Assisted model in learning biology for the 11Th gradestudents of science of SMAN 1 PASIR PENYU which was held on April to May 2015.Theaim of this research is to improve the students competency using the media of studentsworksheet-Assisted model on material “ The sense system” for the 11Th grade students ofscience of SMAN 1 PASIR PENYU.The methodology used in this research is descriptive andthe parameter used was students and teachers activities during the process of learning activityand also students’ cognition, affectivity and psychomotor.The result of this research shows thatthe use of the media of student worksheet-Assisted model can improve the students’competency in mastering the concept of the sense system. The mean score of the daily tests inthe 1st,,2nd and 3rd cycles are : 69.18 , 74.75 and 76.1. the percentage of completeness in the1st,2nd and 3rd cycles are : 65,62% , 71,87% and 87,50%. While the mean student worksheetscore in the 1st,2nd and 3rd cycle are 77.96 , 79.21 and 81.96. The percentage of affective scorein the 1st,2nd and 3rd cycles are : 18,75% , 75% and 81.25% and the percentage of psychomotorscore in the 1st,2nd and 3rd cycles are : 50% , 68.75% and 84.37%. while the percentage ofstudent activity in the 1st,2nd and 3rd cycles are : 59.16% , 70.83% and 85.83% from 32students.Keyword: Kompetensi Belajar Biologi, Media Model Berbantuan LKS.